Legal Protection for Children as a Result of Transnational Marriage Dissolution in Indonesian Marriage Law - Erni Agustin, -
Transnational marriages are common and prevalent in the community. There are legal consequences of transnational marriages, particularly for children born in such marriage. However, the Indonesian Marriage Law does not stipulate any further about the consequences to the children when transnational marriage dissolved or even annulled. This paper aims to elaborate one main issue about the legal protection for children aftermath a transnational marriage dissoulution in accordance with Indonesian Law. Firstly, it discusses the problems that may arise from transnational marriage dissolution for the children. Secondly, this paper will scrutinize the legal protection for children regarding the alimony, custody, and child support when a transnational marriage is dissolved. The analysis is based on the Indonesian Marriage Law and other Laws related to child protection. This paper is a normative legal research using statute and conceptual approaches. This study argues that children have rigths of protection and when a marriage is dissolved, then both parents shall be responsible for the protection and education of their children, solely on the basis of the children’s own best interests.